The Diagnostic Evaluation of Children with Learning Problems: A "Process" Approach. - Ozer, Mark N.; Richardson, Jr., H. Burtt (Journal of Learning Disabilities, 1974)
A protocol for evaluation of children with learning problems was initially designed to identify those children for whom a special education program might be helpful. However, self-contained special education programs are frequently not available and/or not appropriate for the large number of children with learning problems. There is thus a need for diagnostic data which can serve to enhance children's learning within the regular classroom. An evaluation protocol has been developed to produce a diagnosis that is a sampling of some conditions under which a given child's problems with learning may be solved. The protocol defines an interactive process between examiner and child: the examiner responds to the child's attempt to perform a set of prototype tasks with supportive feedback and provides new ways to try the task until the child is successful. The strategies include varying the time provided (programming), kind of input (modality) and at one point in time, the amount of competing stimuli (focusing). During this process the teacher observes the child's actual experience and what can be done to help the child perform certain tasks. The particular strategies used to bring the child to successful performance of the tasks are translated for use in the classroom in relation to tasks defined by the teacher as high priority. Thus what works to help the child in the evaluation process can work to help the child in the classroom. Furthermore, the strategies helpful to the particular child evaluated may be adapted to he/p other children having difficulties as well.